Surveillance for parasites in unaccompanied minor refugees migrating to Germany in 2015 - Heudorf, Ursel (GMS Hyg Infect Control, 2016)
In 2015, most of the refugees arriving in Germany originated from countries with poor hygienic and sanitary conditions. Stool samples of 1,230 minor refugees unaccompanied by adults were investigated for possible parasites. Giardia lamblia was by far the most frequently detected parasite (n=165); all other parasites were considerably less frequent and encountered in the following order: Hymenolepis nana (n=23), Entamoeba histolytica (n=17), Trichuris trichiura (n=8), and Blastocystis hominis (n=1). Ascaris lumbricoides was not detected among any of the screened refugees. Considerable differences in prevalence rates in refugees originating from different countries could be observed.